Improving Motor Vehicle Insurance Claim Efficiency Using Value Stream Mapping - I Made Balik Yudana; Febriana Wurjaningrum; Taufiq Hidayat; Iwan Kresna Setiadi (Yayasan Ilomata, 2026)
This study aims to evaluate and improve the efficiency of the motor vehicle insurance claim process at PT Asuransi Jasaraharja Putera (JRP) through the implementation of Lean Management using Value Stream Mapping (VSM). Data were collected through field observations, in-depth interviews, and analysis of claim documentation from 2021 to 2024. The Current State Map revealed that the average claim completion time was 86 days, significantly exceeding the company’s Service Level Agreement (SLA) of 14 working days. By applying seven VSM tools such as Process Activity Mapping (PAM), Quality Filter Mapping (QFM), and Decision Point Analysis (DPA), the study found that 46% of total activities were non-value-added (NVA). Major inefficiencies were identified in redundant data entry, prolonged approval processes, and manual document handling. The redesigned Future State Map proposes digital process integration and automation to eliminate waste and reduce cycle time. A Fishbone analysis identified six key sources of inefficiency related to human factors, methods, machines, materials, environment, and measurement. The optimized process is projected to reduce claim processing time by approximately 40% and improve customer satisfaction. Overall, this research highlights the novelty of applying VSM for digital process optimization in Indonesia’s insurance industry, demonstrating its effectiveness in enhancing operational efficiency and supporting digital transformation.